2020
DOI: 10.1007/s00101-020-00888-2
|View full text |Cite
|
Sign up to set email alerts
|

Komplikationen und Erfolgsraten des Vena-subclavia-Katheters in Abhängigkeit der Erfahrung

Abstract: Zusammenfassung Hintergrund Die Punktion der V. subclavia gehört zu den Standardprozeduren eines/einer Anästhesisten/Anästhesistin. Gefürchtete Komplikationen dieser Prozedur sind der Pneumothorax und die arterielle Fehlpunktion. Zum Erlernen dieser Prozedur ist von einer gewissen Lernkurve auszugehen. Ziel der Arbeit In dieser Studie soll der Einfluss der Punktionserfahrung auf die Erfolgsquote und mechanische Komplikationen wie Pneumothorax und arterielle Punktion untersucht werden. Dazu sollen 3 Erfahrungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous data indicate that operator training and experience are critical for successful cannulation and low complication rates [ 2 , 25 , 29 , 32 34 ]. This was confirmed in the previous study on the same cohort where limited operator experience was independently associated with a higher risk of both minor and major mechanical complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicate that operator training and experience are critical for successful cannulation and low complication rates [ 2 , 25 , 29 , 32 34 ]. This was confirmed in the previous study on the same cohort where limited operator experience was independently associated with a higher risk of both minor and major mechanical complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a valuable skill, SCV cannulation using landmark technique is associated with patient safety risks. Most clinicians prefer ultrasound-guided IJV cannulation which permits visualization of the vessel (44). A study comparing ultrasound guidance and landmark technique for IJV and femoral access demonstrated that operators learning only the ultrasound-guided technique were not immediately able to perform the landmark technique (increased failure and complication rate).…”
Section: Discussionmentioning
confidence: 99%